The Self’s Micropolis: Representation, Sovereignty and the Individual in the Work of Francisco Giner de los Ríos - Vázquez-Romero, José Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Based on the writings of Giner de los Ríos, this study is about the potentiality of the concept of representation for the analysis of political power within the context of the relationship between the problem of political sovereignty and subjetivization.